2008
DOI: 10.1097/opx.0b013e31818527ea
|View full text |Cite
|
Sign up to set email alerts
|

Reading Speed Does Not Benefit from Increased Line Spacing in AMD Patients

Abstract: Purpose Crowding, the adverse spatial interaction due to the proximity of adjacent targets, has been suggested as an explanation for slow reading in peripheral vision. Previously, we showed that increased line spacing, which presumably reduces crowding between adjacent lines of text, improved reading speed in the normal periphery (Chung, Optom Vis Sci 2004;81:525–35). The purpose of this study was to examine whether or not individuals with age-related macular degeneration (AMD) would benefit from increased lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
(36 reference statements)
0
27
1
Order By: Relevance
“…Recent psychophysical evidence shows that when the disorder has been present for a long time, many people with AMD exhibit characteristics that are more similar to those usually found in the normal fovea, and different from those usually observed in the normal periphery. Such evidence includes the lack of a benefit of reading text with line spacing greater than the standard (Chung et al, 2008; Calabrèse et al, 2010), 4 and that the crowding zone measured at the PRL used by people with AMD is isotropic as in the normal fovea (Toet & Levi, 1992); instead of anisotropic in shape (Chung, 2013b). The changes observed in some spatial properties at the PRL of people with AMD have been attributed to the plasticity of the visual system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent psychophysical evidence shows that when the disorder has been present for a long time, many people with AMD exhibit characteristics that are more similar to those usually found in the normal fovea, and different from those usually observed in the normal periphery. Such evidence includes the lack of a benefit of reading text with line spacing greater than the standard (Chung et al, 2008; Calabrèse et al, 2010), 4 and that the crowding zone measured at the PRL used by people with AMD is isotropic as in the normal fovea (Toet & Levi, 1992); instead of anisotropic in shape (Chung, 2013b). The changes observed in some spatial properties at the PRL of people with AMD have been attributed to the plasticity of the visual system.…”
Section: Discussionmentioning
confidence: 99%
“…Bentley 10 , Peterson and Tinker 11 , examined the effect of line spacing on reading speed and concluded thatincreased vertical word spacing, benefits reading speed.Similar result is obtained in present study but up to a spacing of 3x Calabrese A. et.al. 15 concluded that increasing interline spacing is advisable only for very slow readers (<20 words/min) who want to read a few words (spot reading). Vertical crowding does not seem to be a major determinant of maximal reading speed for patients with central scotoma while Chung ST 15 et al concluded that increased line spacing in passages, or increased vertical separation between words in RSVP (rapid serial visual presentation), did not lead to improved reading speed in people with AMD.Rubin GS 9 statedthat line width and typeface have little influence on reading speed in people with mild to moderate sight problems.In our study, we have not considered specific group of disease but overall low vision subjects.…”
Section: Resultsmentioning
confidence: 99%
“…15 concluded that increasing interline spacing is advisable only for very slow readers (<20 words/min) who want to read a few words (spot reading). Vertical crowding does not seem to be a major determinant of maximal reading speed for patients with central scotoma while Chung ST 15 et al concluded that increased line spacing in passages, or increased vertical separation between words in RSVP (rapid serial visual presentation), did not lead to improved reading speed in people with AMD.Rubin GS 9 statedthat line width and typeface have little influence on reading speed in people with mild to moderate sight problems.In our study, we have not considered specific group of disease but overall low vision subjects. Future studies are required in low vision subjects to assess reading speed in central and peripheral field loss separately.…”
Section: Resultsmentioning
confidence: 99%
“…Past attempts to improve peripheral reading via crowding reduction have generally focused on introducing spatial changes to the stimulus, such as increasing letter spacing (Chung, 2002), enlarging the spacing between lines of text (Bernard, Anne-Catherine, & Eric, 2007;Calabrèse et al, 2010;Chung, 2004;Chung, Jarvis, Woo, Hanson, & Jose, 2008), and decreasing the spatial similarity of adjacent letters (Chung & Mansfield, 2009). However, despite the critical importance of spacing and spatial similarity to crowding, these manipulations have limited effectiveness in improving peripheral reading.…”
Section: Introductionmentioning
confidence: 98%